2014
DOI: 10.1080/09540121.2014.963496
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitudes towards HIV/AIDS among residents of Kandy, Sri Lanka

Abstract: Currently, interventions for HIV/AIDS control in Sri Lanka are only carried out among the mostat-risk populations. This study was conducted to identify the level of awareness and stigma related attitudes among the general population of Sri Lanka. A cross-sectional study was carried out among 869 residents of 18-64 years of age in Kandy, Sri Lanka. A self-administered questionnaire was utilised to obtain information about stigma, discrimination and HIV/AIDSrelated knowledge. Chi square test and multivariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…In our study, the awareness rate of Ebola virus disease was 38.07 %, which is similar to Jain's study that 52.4 % respondents had a higher level of cognition while 2.8 % had a lower level of knowledge about Ebola virus disease [15]. The awareness rate of HIV/AIDS was 81.04 % as same as Sutton's [16] survey, but higher than Navaratna's [17] study. The difference about awareness rate concerning two diseases might be due to less attention because of no outbreak about Ebola virus disease in China or lack of enough, active, effective propaganda and health education on it.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In our study, the awareness rate of Ebola virus disease was 38.07 %, which is similar to Jain's study that 52.4 % respondents had a higher level of cognition while 2.8 % had a lower level of knowledge about Ebola virus disease [15]. The awareness rate of HIV/AIDS was 81.04 % as same as Sutton's [16] survey, but higher than Navaratna's [17] study. The difference about awareness rate concerning two diseases might be due to less attention because of no outbreak about Ebola virus disease in China or lack of enough, active, effective propaganda and health education on it.…”
Section: Discussionsupporting
confidence: 78%
“…Comparison in different socio-demographic, awareness rates about Ebola virus disease and HIV/AIDS among medical students were all higher than non-medical; awareness rate about Ebola virus disease and HIV/AIDS in different grades all had statistic significance, as the same as Okafor's study about HIV [21], but had not statistic significance in different sex as the conclusion in Navaratna's study [17]; different registered residences participants had statistic significance in Ebola virus disease but not in HIV/AIDS 19 . So WHO suggested that we should promote health education [22].…”
Section: Discussionsupporting
confidence: 57%
“…Similar results were found to be reported in Sri Lanka. However, Janahi and colleagues in their findings reported that more than half of the adult participants (n = 1,630) in Bahrain would avoid sitting near, hugging or even shaking HIV infected people's hand [110][111][112].…”
Section: Discussionmentioning
confidence: 99%
“…Receiving the HIV risk self-assessment conducted by the school and awareness that HIV self-testing kits were available at school were influencing factors, and knowledge of HIV/AIDS prevention and treatment was a protective factor against casual sexual behavior among male college students. Studies have shown that increasing the population's HIV/AIDS awareness rate and promoting consistent knowledge and behaviors are important means to protect susceptible populations [18,19]. It is necessary to further strengthen campus health education and increase publicity to promote the integration of knowledge and actions to prevent HIV infection.…”
Section: Plos Onementioning
confidence: 99%